Saint Annes Church in Mazagaon - Mumbai Archive Project Team (Jio Institute, 2024)
Saint Annes Church in Mazagaon showcases pointed arches, ribbed vaults, and lofty spires, all hallmarks of the neo-Gothic style. The cornerstone was set on April 10, 1880, and on November 6, 1881, Bombay Bishop Meurin dedicated it.